The Role of Teachers in Optimizing Scientific-Based Learning in Elementary Schools: Peran Guru dalam Optimalisasi Pembelajaran Berbasis Saintifik di Sekolah Dasar - Khasana, Nur; Nurdiansyah, Nurdiansyah (Indonesian Journal of Education Methods Development, 2022)
This study aims to find out what the teacher's role is in optimizing scientific-based learning at SDN Rangkah Kidul Sidoarjo. This study uses qualitative research using a phenomological approach. This approach uses field research. The findings of the data at SDN Rangkah Kidul in the role of teachers in optimizing scientific-based learning are that all teachers have taught scientific-based learning, namely teachers use several tools in scientific learning such as using the methods they teach and making designs before learning takes place and making evaluation of scientific-based learning. Besides that, teachers also face obstacles in using scientific learning due to the difficulty of teachers finding other methods in understanding their students and the lack of learning media where teachers have difficulty finding ideas in the learning process.